2005
DOI: 10.1016/j.neuroimage.2005.05.045
|View full text |Cite
|
Sign up to set email alerts
|

High gamma frequency oscillatory activity dissociates attention from intention in the human premotor cortex

Abstract: The premotor cortex is well known for its role in motor planning. In addition, recent studies have shown that it is also involved in nonmotor functions such as attention and memory, a notion derived from both animal neurophysiology and human functional imaging. The present study is an attempt to bridge the gap between these experimental techniques in the human brain, using a task initially designed to dissociate attention from intention in the monkey, and recently adapted for a functional magnetic resonance im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
107
0

Year Published

2006
2006
2011
2011

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 150 publications
(133 citation statements)
references
References 35 publications
(46 reference statements)
16
107
0
Order By: Relevance
“…Next to their clinical importance, invasive recordings offer unique opportunities for electrophysiological investigations of human brain function with high spatial and temporal accuracy. An increasing number of studies have recently investigated motor Brovelli et al, 2005;Crone et al, 1998;Rektor, 2000;Szurhaj et al, 2006), sensory (Crone et al, 2001a;Edwards et al, 2005;Steinschneider et al, 2005), and cognitive (Canolty et al, 2006;Crone et al, 2001b;Ray et al, 2008;Sederberg et al, 2007;Sinai et al, 2005) systems using invasive EEG data. Furthermore, ECoG recordings have been proposed as a technology for brain-machine interfaces (BMIs) for neuronal motor prostheses in paralyzed patients (Ball et al, 2009;Leuthardt et al, 2004;Mehring et al, 2004;Pistohl et al, 2008;Schalk et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Next to their clinical importance, invasive recordings offer unique opportunities for electrophysiological investigations of human brain function with high spatial and temporal accuracy. An increasing number of studies have recently investigated motor Brovelli et al, 2005;Crone et al, 1998;Rektor, 2000;Szurhaj et al, 2006), sensory (Crone et al, 2001a;Edwards et al, 2005;Steinschneider et al, 2005), and cognitive (Canolty et al, 2006;Crone et al, 2001b;Ray et al, 2008;Sederberg et al, 2007;Sinai et al, 2005) systems using invasive EEG data. Furthermore, ECoG recordings have been proposed as a technology for brain-machine interfaces (BMIs) for neuronal motor prostheses in paralyzed patients (Ball et al, 2009;Leuthardt et al, 2004;Mehring et al, 2004;Pistohl et al, 2008;Schalk et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Human electroencephalography (EEG) studies provided evidence that oscillatory activity in the gamma band is correlated with the perception of coherent objects (Keil et al, 1999;Rodriguez et al, 1999;Gruber and Müller, 2005;Martinovic et al, 2008). Most EEG gamma-band studies have focused on lower gamma-band frequencies (Ͻ60 Hz); however, recent magnetoencephalography (MEG) and intracranial EEG studies have shown that oscillations in the high-frequency gamma band (Ͼ60 Hz) are reliable markers of cortical activity during a variety of cognitive tasks (Crone et al, 2001;Kaiser et al, 2004;Brovelli et al, 2005;Lachaux et al, 2005;Hoogenboom et al, 2006;Vidal et al, 2006;Guggisberg et al, 2007;Siegel et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…Recent iEEG studies have put a strong emphasis on gamma band activations in particular, in association with a wide range of cognitive processes, including memory (Fell et al, 2001;Howard et al, 2003;Mainy et al, 2007), visual attention and perception (Brovelli et al, 2005;Lachaux et al, 2000Lachaux et al, , 2005Tallon-Baudry et al, 2005;Tanji et al, 2005), audition (Bidet-Caulet et al, 2003;Edwards et al, 2005), somatosensory and motor processes Crone, Sinai and Korzeniewska, 2006;Lachaux et al, 2005;Aoki et al, 1999;Pfurtscheller et al, 2003;Szurhaj et al, 2005), and language . Importantly, in all those studies, gamma band activity was observed only in very specific brain regions, dependant on the tasks, and in good agreement with the functional networks revealed by fMRI .…”
Section: Introductionmentioning
confidence: 99%